The socio-economic impact of roads on rural communities : a case study on the longhouses communities of rumah ukan, rumah jandok and rumah bundong of ulu bukit guram-ulu yong road - Manjah, Frankie Bendindang (Faculty of Social Sciences, 2005)
Rural development is one of the major agendas of the Third World countries. Many development programmes have been channelled and implemented to improve the livelihood of the rural community. Development pf rural roads is to connect the remote rural community to have access to the urban infrastructure such as basic amenities and marketing outlet of their agriculture produce.